Comprehensive Analysis of the Effects of Genetic Ancestry and Genetic Characteristics on the Clinical Evolution of Oral Squamous Cell Carcinoma - Guo, Junfeng; Liu, Xiaoping; Zeng, Yi; Liang, Taotao; Tang, Kanglai; Guo, Junfeng; Zheng, Weiwei (Frontiers in Cell and Developmental Biology, 2021)
Oral squamous cell carcinoma (OSCC), a kind of malignant cancer, is associated with increasing morbidity and mortality. Patients with different genetic ancestries may respond differently to clinical treatment. The limited understanding of the influence of genetic ancestry and genetic characteristics on OSCC impedes the development of precision medicine. To provide a reference for clinical treatment, this study comprehensively analyzed multigenomic differences in OSCC patients with different genetic ancestries and their impact on prognosis. An analysis of data from OSCC patients with different genetic ancestries in The Cancer Genome Atlas (TCGA) showed that the overall survival (OS) of African (AFR) patients was lower than that of primarily European (EUR) patients, and differences were also observed in the tumor–stroma ratio (TSR) and tumor-infiltrating lymphocytes (TILs), which are associated with prognosis. FAT1 is a key mutant gene in OSCC, and it has inconsistent effects on clinical evolution for patients with diverse genetic characteristics. PIKfyve and CAPN9 showed a significant difference in mutation frequency between EUR and AFR; PIKfyve was related to Ki-67 expression, suggesting that it could promote tumor proliferation, and CAPN9 was related to the expression of Bcl-2, promoting tumor cell apoptosis. A variant methylation locus, cg20469139, was correlated with the levels of PD-L1 and Caspase-7 and modulated tumor cell apoptosis. A novel ceRNA model was constructed based on genetic ancestries, and it could accurately evaluate patient prognosis. More importantly, although T cell dysfunction scores could determine the potential of tumor immune escape, the efficacy was obviously affected by patients’ genetic ancestries. To provide patients with more precise, personalized therapy and to further improve their quality of life and five-year survival rate, the influence of genetic ancestry should be fully considered when selecting treatments.